2014
DOI: 10.5713/ajas.2013.13394
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aviary, Barn and Conventional Cage Raising of Chickens on Laying Performance and Egg Quality

Abstract: This study intended to compare the productive performance of three different layer raising systems; conventional cage (CC), barn (BR) and aviary (AV). The AV is welfare bestowed housing that allows free locomotion for birds within the BR. The BR allows bird’s free locomotion inside BR but without multilevel structures. Both pullets and cockerels were housed together in both AV and BR, but only pullets in CC. Seventeen weeks old Lohmann Brown Lite (n = 800) pullets were housed in AV during this study. The same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
29
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 22 publications
10
29
3
3
Order By: Relevance
“…Lower albumen height caused the lower albumen index of an egg. Singh et al (2009) and Ahammed et al (2014) found lower albumen height in eggs from floor than cage system, which was also the case in present research. Lower albumen height of eggs may be due to their exposure to ammonia (from litter) which affects albumen quality (Roberts, 2004).…”
Section: Resultssupporting
confidence: 88%
“…Lower albumen height caused the lower albumen index of an egg. Singh et al (2009) and Ahammed et al (2014) found lower albumen height in eggs from floor than cage system, which was also the case in present research. Lower albumen height of eggs may be due to their exposure to ammonia (from litter) which affects albumen quality (Roberts, 2004).…”
Section: Resultssupporting
confidence: 88%
“…However, Englmaierová et al (18) observed that the albumen and yolk index were higher in enriched cages and aviaries. In the present study, eggs from the FR system had the highest shape index and yolk index values among all of the housing systems, but some other researchers found that housing system did not affect yolk index and shape index (15,19).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies compared traditional cages with other housing systems and observed thicker egg shells and better breaking strength in aviary and barn eggs (15,20). In the present study, housing systems did not affect egg shell thickness and shell breaking strength.…”
Section: Discussionmentioning
confidence: 99%
“…There was a statistical difference between organic and freerange groups on analysis of the effect of rearing systems on shell thickness (p<0.05) ( Table 1). Studies on this subject, similarly found significant effect of rearing systems on shell thickness 1,3,9,17,18 . Contrarily, there are studies, which did not find a statistical difference between rearing systems and shell thickness 4,16,19 .…”
Section: Discussionmentioning
confidence: 81%